Competencies of nursing faculty in selected colleges of nursing as assessed by themselves and students in Cabanatuan City Nueva Ecija: an assessment - Hermosa, Manuel L. (Manila : National University, 2009)
The study aimed to assess the competencies of nursing faculty in selected colleges of nursing in Cabanatuan City, Nueva Ecija. It was delimited to 240 respondents. The study was conducted during the whole month of October 2008.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices .
Research Method: Descriptive Design.
Includes bibliographical references.